Blockchain-Based Evidence and Legal Validity: Reformulating Norms for Decentralized Justice Systems - Carlos Pérez; Isabel López; Francisco López (Rechtsnormen: Journal of Law, 2025)
Background. The increasing integration of blockchain technology into legal frameworks necessitates a critical re-evaluation of how evidence and legal validity are conceptualized within decentralized justice systems. Traditional jurisprudence relies on centralized authority for the authentication and admissibility of evidence. However, blockchain’s immutable and decentralized nature offers new paradigms for trust, transparency, and verification raising both opportunities and challenges in adapting current legal norms. Purpose. This study aims to explore the legal implications of blockchain-based evidence, focusing on the reformulation of evidentiary and procedural standards in decentralized environments. Method. Using a qualitative juridical-normative method, this research analyzes comparative case studies, statutory instruments, and international best practices in blockchain jurisprudence. Results. The results demonstrate a significant gap in current legal structures regarding the recognition and standardization of digital ledger evidence. Key challenges include the absence of uniform protocols, jurisdictional discrepancies, and the epistemological shift required in legal reasoning. Conclusion. This study concludes that a comprehensive legal framework is imperative to ensure the legitimacy and enforceability of blockchain-generated evidence. Reformulating evidentiary norms aligned with decentralized principles is not only necessary but urgent to uphold justice in emerging digital ecosystems.